Modified polypropylene dielectric energy storage material as well as preparation method and application thereof

By introducing graft monomers and other additives into the polypropylene film capacitors and melt-kneading to prepare modified polypropylene dielectric energy storage materials, the problem of poor energy storage performance of polypropylene film capacitors at high temperatures is solved, and high temperature stability and industrial production are achieved.

CN119912641APending Publication Date: 2025-05-02CHINA PETROLEUM & CHEMICAL CORP +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311434868.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-31
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

Polypropylene film capacitors have poor dielectric energy storage performance under high temperature conditions, and the existing methods have complex processes for preparing high-temperature stable polymer capacitor films, making it difficult to produce large-scale industrialized.

Method used

Modified polypropylene dielectric energy storage material with good grafting effect is prepared by mixing and melt-kneading polypropylene, graft monomer, initiator, antioxidant, dispersant and other additives.

Benefits of technology

The modified polypropylene dielectric energy storage material exhibits good energy storage and stability at high temperatures, has a relatively simple process and is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004525404080000131
    Figure BDA0004525404080000131
  • Figure BDA0004525404080000132
    Figure BDA0004525404080000132
  • Figure BDA0004525404080000141
    Figure BDA0004525404080000141
Patent Text Reader

Abstract

The invention belongs to the technical field of polymers, and discloses a modified polypropylene dielectric energy storage material as well as a preparation method and application thereof. The preparation method comprises the following steps: mixing polypropylene, a grafting monomer, an initiator, an antioxidant, a dispersing agent and optional other auxiliaries, and melting and mixing to obtain the modified polypropylene dielectric energy storage material, wherein the ash content of the polypropylene is less than 55 ppm, preferably less than 40 ppm, and more preferably less than 36 ppm. The prepared modified polypropylene dielectric energy storage material has a good grafting effect, so that the modified polypropylene dielectric energy storage material has good high-temperature energy storage performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of polymer technology, and more specifically, to a modified polypropylene dielectric energy storage material and a preparation method and application thereof. Background Art

[0002] Polymer film capacitors have obvious advantages over other types of capacitors, among which the most commercially used dielectric material is biaxially oriented polypropylene (BOPP). However, an inherent disadvantage of polypropylene film capacitors is that the dielectric energy storage performance is poor and the reliability is greatly reduced under high temperature conditions. The life span is halved for every 8°C increase in temperature. The long-term stable operating temperature of BOPP capacitors under higher electric fields is only 85°C, and the highest operating temperature of currently known commercial high-temperature BOPP films is only 105°C. As the installed capacity and scale of photovoltaic power generation and offshore wind power continue to increase, the demand for BOPP capacitor films with higher operating temperatures is becoming increasingly strong.

[0003] At present, there are two main methods to improve the working temperature of polymer capacitor films from the perspective of materials. The first method is to improve the thermal stability of polymer dielectric materials, that is, to synthesize polymer dielectric materials with high glass transition temperature (T g ) polymer dielectric material. The second method is to introduce a second phase filler into the polymer dielectric material to prepare a composite material, and use the capture and scattering effect of the filler particles on carriers to suppress the leakage current of the polymer under high temperature and high electric field. However, both methods have the problem of complex preparation process and difficulty in large-scale industrial production.

[0004] Graft modification is a common means of functionalizing polypropylene. Functional monomer side chains are introduced into the main chain of polypropylene through free radical reaction to change the molecular band structure of polypropylene and introduce charge traps, thereby improving the dielectric properties of polypropylene. In CN202210945889.5, a capacitor film with high energy storage and dielectric properties at high temperature is prepared by suspension and solid phase grafting on low-ash polypropylene. However, the invention does not mention the application of the melt grafting method. Summary of the invention

[0005] The purpose of the present invention is to provide a modified polypropylene dielectric energy storage material and a preparation method and application thereof. The modified polypropylene dielectric energy storage material prepared by the present invention has a good grafting effect, thereby making the modified polypropylene dielectric energy storage material have good high-temperature energy storage properties.

[0006] In order to achieve the above-mentioned object, the first aspect of the present invention provides a method for preparing a modified polypropylene dielectric energy storage material, the preparation method comprising: mixing and melt-kneading polypropylene, a grafting monomer, an initiator, an antioxidant, a dispersant and other optional additives to obtain the modified polypropylene dielectric energy storage material;

[0007] Wherein, the ash content of the polypropylene is less than 55 ppm, preferably less than 40 ppm, and more preferably less than 36 ppm.

[0008] The second aspect of the present invention provides a modified polypropylene dielectric energy storage material prepared by the above preparation method.

[0009] The third aspect of the present invention provides the use of the modified polypropylene dielectric energy storage material in the preparation of energy storage dielectrics; preferably in the preparation of high-temperature energy storage dielectrics;

[0010] The dielectric is preferably a single-layer or multi-layer film dielectric;

[0011] The membrane dielectric is preferably a capacitor film, a roughened film, a supercapacitor film, an electrostatic film or a battery separator, and is more preferably a capacitor film.

[0012] The technical solution of the present invention has the following beneficial effects:

[0013] (1) The modified polypropylene dielectric energy storage material prepared by the present invention has a good grafting effect, thereby making the modified polypropylene dielectric energy storage material have good high-temperature energy storage properties.

[0014] (2) The present invention effectively improves the diffusion and dispersion uniformity of the initiator and the grafted monomer in the resin by selecting polypropylene of a specific particle size and adopting a premixing method, so that the material obtains more excellent dielectric energy storage performance.

[0015] (3) The present invention effectively inhibits side reactions such as polypropylene degradation by selecting polypropylene, grafting monomers, reaction conditions and a composite initiator system, thereby maintaining good processing, mechanical and dielectric properties of the material.

[0016] Other features and advantages of the present invention will be described in detail in the following detailed description. DETAILED DESCRIPTION

[0017] The preferred embodiments of the present invention will be described in more detail below. Although the preferred embodiments of the present invention are described below, it should be understood that the present invention can be implemented in various forms and should not be limited to the embodiments set forth herein.

[0018] The first aspect of the present invention provides a method for preparing a modified polypropylene dielectric energy storage material, the preparation method comprising: mixing and melt-kneading polypropylene, a grafting monomer, an initiator, an antioxidant, a dispersant and other optional additives to obtain the modified polypropylene dielectric energy storage material;

[0019] Wherein, the ash content of the polypropylene is less than 55 ppm, preferably less than 40 ppm, and more preferably less than 36 ppm.

[0020] According to the present invention, preferably, the preparation method comprises:

[0021] (1) stirring the grafting monomer, the initiator and optionally a portion of the dispersant to obtain a mixed solution;

[0022] (2) mixing the polypropylene and the mixed solution to obtain prefabricated polypropylene particles;

[0023] (3) The antioxidant, the remaining dispersant and the other additives are mixed; then mixed with the prefabricated polypropylene particles, melt-kneaded, and the modified polypropylene dielectric energy storage material is obtained.

[0024] In the present invention, preferably, the material mixing operation in step (2) and the mixing operation with the prefabricated polypropylene particles in step (3) are both performed under inert gas conditions.

[0025] In the present invention, the sum of the amounts of the optional part of the dispersant and the remaining dispersant is the amount of the total dispersant. When the amount of the optional part of the dispersant is 0, the amount of the remaining dispersant is the amount of the total dispersant.

[0026] According to the present invention, preferably, the melt flow rate of the polypropylene at 230° C. and a load of 2.16 kg is 0.01 to 10 g / 10 min, preferably 0.5 to 10 g / 10 min, and more preferably 2 to 5 g / 10 min.

[0027] In the present invention, preferably, the polypropylene can be a homopolypropylene or a propylene copolymer containing ethylene and / or butene copolymer. Homopolypropylene is preferably a homopolypropylene with an isotacticity greater than 96%, and more preferably a homopolypropylene with an isotacticity greater than 96.5%; preferably, the total content of copolymerized units in the copolymerized polypropylene is greater than 0 and less than 0.1 mol%, or greater than 0.1 mol% and less than or equal to 3.0 mol%.

[0028] In the present invention, the polypropylene powder suitable for the present invention can be commercially available, or prepared by the methods described in patent applications CN109694427A, CN109694428A, CN104558813A, CN109912734A, CN111019025A, and CN105431459A.

[0029] In the present invention, the grafting monomer is a compound containing an olefinic bond and one or more other functional groups in one molecule. The functional group may be one or more of an aromatic ring, a hydroxyl group, an amino group, an epoxy group, an unsaturated carboxylic acid, an amide group, an imide group, an ester group, an alkoxysilane group, an acyl halide group, a cyano group, an anhydride group, a nitrogen-containing heterocyclic group, an allyl group, etc. Including but not limited to one or more of acrylates, acrylic acid, maleic anhydride, styrene monomers, acrylonitrile, vinyl acetate, vinyl chloride, glycidyl methacrylate, trimethoxysilane, vinyl pyridine, vinylimidazole and vinyl pyrrolidone. Among them, one or more of styrene, triethoxysilane, glycidyl methacrylate and maleic anhydride are preferred. The grafting monomer may be one or more of the above compounds. Preferably, the grafting monomer is at least one of aromatic olefins, anhydrides, acrylic acid and acrylic acid esters; more preferably, at least one of styrene, maleic anhydride, glycidyl methacrylate, methyl methacrylate and acrylic acid.

[0030] The grafting monomer can directly participate in the grafting reaction in the form of a monomer, or can be prepolymerized into a polymer form and then participate in the grafting reaction.

[0031] According to the present invention, preferably, the initiator is a peroxide and / or an azo initiator;

[0032] Preferably, the peroxidation initiator comprises at least one of benzoyl peroxide, dichlorobenzoyl peroxide, dialkyl peroxide, aralkyl peroxide, peroxyester and peroxycarbon ester; preferably, it is a compound of diisopropylbenzene peroxide (DCP), tert-butyl peroxy-2-ethylhexanoate (TBPEH), di-tert-butyl peroxide (DTBP) and tert-butyl peroxybenzoate (TBPB); more preferably, it is a compound of tert-butyl peroxy-2-ethylhexanoate (TBPEH) and tert-butyl peroxybenzoate (TBPB) or a compound of tert-butyl peroxy-2-ethylhexanoate (TBPEH) and diisopropylbenzene peroxide (DCP).

[0033] In the present invention, the dispersant is added, mainly used for the dispersing and diffusion of the initiator, the grafting monomer, the antioxidant and other auxiliary agents. The dispersant is a liquid dispersant, preferably at least one of an aromatic hydrocarbon solvent, an aliphatic hydrocarbon solvent, an alicyclic hydrocarbon solvent, a chlorinated hydrocarbon, an alcohol solvent, a ketone solvent, an ester solvent and an ether solvent, and more preferably at least one of benzene, toluene, xylene, pentane, hexane, heptane, octane, nonane, decane, cyclohexane, methylcyclohexane, decahydronaphthalene, chlorobenzene, dichlorobenzene, trichlorobenzene, methylene chloride, chloroform, carbon tetrachloride, tetrachloroethylene, methanol, ethanol, propynol, isopropyl alcohol, n-butanol, 2-butanol, isobutyl alcohol, tert-butanol, acetone, methyl ethyl ketone, methyl isobutyl ketone, ethyl acetate, dimethyl phthalate, dimethyl ether, ethyl ether, di-n-amyl ether, tetrahydrofuran and dioxyanisole.

[0034] In the present invention, the antioxidant is selected from at least one of hindered phenols, hindered amines, phosphites, thiols and benzofuranones. Preferably, it is selected from pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate (antioxidant 1010), tris[2,4-di-tert-butylphenyl]phosphite (antioxidant 168), β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate n-octadecyl alcohol (antioxidant 1076), 2,2'-thiobis[3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate] (antioxidant 1035), 2,2'-methylenebis(4-methyl-6-tert-butylphenol) (antioxidant 2246), 1,1,3-tris(2-methyl-4-hydroxy-5-tert-butylphenol) At least one of bis(2,4-di-tert-butylphenol)pentaerythritol diphosphite (antioxidant 626), 3-butyl-1(3-hydrogen)-isobenzofuranone (antioxidant 501), 5-methyl-7-tert-butyl-3-(3,4-dimethyl)-3-hydrogen-benzofuran-2-one, 5-methyl-7-tert-butyl-3-(2,5-dimethyl)-3-hydrogen-benzofuran-2-one, and 5-methyl-7-tert-butyl-3-(2-hydroxy-5-methyl)-3-hydrogen-benzofuran-2-one; more preferably, a mixture of two or three of the above antioxidants.

[0035] Preferably, the antioxidant is compounded from an antioxidant component A and an antioxidant component B, wherein the antioxidant component A is selected from at least one of hindered phenols, hindered amines, phosphites and thiols, and the antioxidant component B is at least one benzofuranone;

[0036] More preferably, it is at least one of the antioxidant 1010 , the antioxidant 168 , and the antioxidant 501 .

[0037] In the method of the present invention, a common processing aid may be optionally added. Preferably, the other additives include at least one of an antidegradant, a nucleating agent, a lubricant, an acid absorbent, a slip agent, an antistatic agent and an anti-adhesive agent. The dosage of the above various additives can be a conventional choice in the art, which is known to those skilled in the art and will not be described in detail here. The processing aid used will not have an adverse effect on the stretch film-forming property and mechanical properties of the modified polypropylene material.

[0038] In the present invention, preferably, the antidegradant includes at least one of styrene, α-methylstyrene, trimethylolpropane triacrylate (TRIS) and divinylbenzene (DVB), preferably styrene. The mass ratio of the antidegradant to the grafting monomer is 0.01 to 1:1. The antidegradant can effectively increase the grafting rate and inhibit the degradation of polypropylene.

[0039] In the present invention, preferably, the other auxiliary agent is a lubricant and / or a fluorine-containing polymer.

[0040] The lubricant can be selected from one or more of polyethylene glycol lubricants, fluorine-containing polymer lubricants, silicone lubricants, fatty alcohol lubricants, fatty acid lubricants, fatty acid ester lubricants, stearic acid amide lubricants, fatty acid metal soap lubricants, alkanes and oxidized alkanes lubricants and micro-nanoparticle lubricants.

[0041] Specifically, the PEG lubricant can be, for example, a PEG molecule with a molecular weight of 500 to 50,000, which can be subjected to end-capping, grafting, cross-linking treatment, or other chemical or physical modifications. The fluoropolymer lubricant can be, for example, at least one of polytetrafluoroethylene, polyvinylidene fluoride, polyhexafluoropropylene, etc., or other unimodal or multimodal fluoropolymers and crystalline or semi-crystalline fluoropolymers. The organosilicon lubricant can be various existing compounds with carbon and silicon atoms as the main molecular chain and oligomers or oligomers of organic groups such as methyl, phenyl, alkoxy, vinyl, etc. as side chains. The fatty alcohol lubricant can be, for example, at least one of soft fatty alcohol, stearic alcohol, tallow fatty alcohol, etc. The fatty acid lubricant can be, for example, stearic acid and / or 12-hydroxystearic acid. The fatty acid ester lubricant can be, for example, at least one of butyl stearate, stearic acid monoglyceride, palmitic acid hexadecyl ester, stearic acid octadecyl ester, etc. The stearic acid amide lubricant may be, for example, at least one of stearic acid amide, oleic acid amide, erucic acid amide, n,n-ethylene bis stearic acid amide (EBS), etc. The fatty acid metal soap lubricant may be, for example, at least one of lead stearate, calcium stearate, magnesium stearate, synthetic calcium acetate, etc. The alkane and alkane oxide lubricant may be, for example, at least one of liquid paraffin, paraffin wax, polyethylene wax, polypropylene wax, ethylene oxide wax, etc. The micro-nano particle lubricant may be, for example, powdered rubber and / or silica gel particles.

[0042] In order to improve the performance of the dielectric film, the dielectric film preferably further contains a film-forming aid. The film-forming aid can be selected from at least one of an anti-halogen agent, a light stabilizer, a heat stabilizer, a colorant, a filler, a lubricant, an anti-adhesive agent and an antistatic agent. The specific type of the film-forming aid is a conventional choice in the art and will not be described in detail here.

[0043] All of the above processing aids are commercially available.

[0044] According to the present invention, preferably, the temperature of the melt kneading is 120 to 250°C, preferably 130 to 220°C, and more preferably 160 to 220°C;

[0045] In parts by mass, relative to 100 parts of the polypropylene, the amount of the grafting monomer is 0.1 to 30 parts, preferably 2 to 15 parts, the amount of the initiator is 0.001 to 10 parts, preferably 0.1 to 2 parts, the amount of the antioxidant is 0.1 to 0.8 parts, preferably 0.1 to 0.6 parts, the amount of the dispersant is 0.01-10 parts and the amount of the optional other auxiliary agents is 0 to 1 part, preferably 0 to 0.6.

[0046] In the present invention, preferably, the reaction equipment can adopt single screw extruder, twin screw extruder, internal mixer, mixer, rheometer, kneader and other common melt mixing equipment in the field of polyolefin processing. These methods can be used in combination or alone. Preferably, a reactive twin screw extruder and / or a single screw extruder is used, more preferably a reactive twin screw extruder, and further preferably a reactive twin screw extruder with a length-to-diameter ratio greater than 25.

[0047] In the present invention, a low melt mixing temperature is not conducive to the grafting reaction, while a high temperature is likely to cause polypropylene degradation.

[0048] In the present invention, preferably, the melt mixing time is 0.1 to 30 minutes, preferably 0.5 to 10 minutes; too short a melt mixing time is not conducive to the conversion rate of the grafting reaction, and too long a time is likely to cause polypropylene degradation; if the reaction equipment is a twin-screw extruder, the rotation speed is between 30 and 400 rpm, preferably 150 to 250 rpm.

[0049] In the present invention, preferably, all raw materials can be fully mixed and added to the reaction equipment at one time, or added to the reaction equipment step by step, or some components can be pre-mixed and then mixed with other components, including but not limited to adding grafted monomers after polypropylene is melted, and then adding a mixture of initiator and dispersant; polypropylene and grafted monomers are mixed and melted, and then initiator and other additives are added. The pre-mixing of raw materials can adopt the solid or solid-liquid mixing method commonly used in the industry, such as high-speed or low-speed stirring equipment; or select a solvent with good solubility for grafted monomers and initiators and low boiling point as a dispersant, dissolve the grafted monomers and initiators and then mix them with the resin, and then vacuum or evaporate the low boiling point solvent to obtain a raw material mixture.

[0050] As a preferred implementation method of the present invention, the implementation method includes:

[0051] (1) stirring an initiator, a grafting monomer and an optional portion of a dispersant at 40° C. for 10 to 30 minutes to form a uniform solution;

[0052] (2) sieving polypropylene powder with a particle size of 0.5 to 2 mm;

[0053] (3) adding the solution obtained in step (1) into a mixer containing the polypropylene powder at a rate of 5-20 ml / min, and after the addition is completed, mixing at 40-60° C. for 0.5-2 hours to obtain prefabricated polypropylene particles;

[0054] (4) mixing the antioxidant, the remaining dispersant and other optional additives into a uniform solution, adding the solution into the mixer and mixing for 10 to 20 minutes, and optionally evacuating the mixture to obtain a mixed raw material;

[0055] (5) The mixed raw materials are put into a twin-screw extruder, melt-mixed, extruded, cooled and pelletized at 160-220° C. and a rotation speed of 140-200 rpm to obtain a modified polypropylene dielectric energy storage material.

[0056] In the above preferred implementation method, in step (4), adding the mixer refers to adding the mixer containing the prefabricated polypropylene particles in step (3).

[0057] In the above preferred implementation method, the material mixing operation in step (3) and the operation of mixing with the prefabricated polypropylene particles in the mixer in step (4) are preferably carried out under inert gas conditions.

[0058] In the present invention, the polypropylene is preferably a polypropylene powder with a particle size of 0.5 to 2 mm; preferably, the particle size of the polypropylene powder can be controlled to be 0.5 to 2 mm by particle size screening. Common screening methods are well known to those skilled in the art, such as screening by using a mechanical vibrating screen equipped with sieves of different mesh sizes (10 mesh and 35 mesh).

[0059] The second aspect of the present invention provides a modified polypropylene dielectric energy storage material prepared by the above preparation method.

[0060] According to the present invention, preferably, the modified polypropylene dielectric energy storage material has at least one of the following physical properties: a melt flow rate of 1 to 10 g / 10 min at 230° C. and a load of 2.16 kg, preferably 1.5 to 8 g / 10 min, and more preferably 2 to 5 g / 10 min;

[0061] Ash content less than 50 ppm, preferably less than 36 ppm;

[0062] The grafting amount is 0.01 to 10 wt%, preferably 0.1 to 8 wt%;

[0063] The maximum operating temperature of the modified polypropylene dielectric energy storage material is ≥100°C, preferably 105-145°C;

[0064] The breakdown field strength at 110°C is Eg ≥ 580 MV / m, preferably 600-800 MV / m;

[0065] DC volume resistivity ρ at 110℃ and 200MV / m field strength vg ≥1.1×10 14 Ω·m, preferably 2.1×10 14 Ω·m~1.0×10 20 Ω·m;

[0066] The dielectric constant at 110°C and 100 Hz is greater than 2.3, preferably 2.4 to 2.7;

[0067] The dielectric loss at 110℃ and 100Hz is less than 1.1×10 -3 , preferably 1.0×10 -6 ~9.5×10 -4 ;

[0068] The energy storage density at 110°C and 200MV / m is greater than 0.750J / cm 3 , preferably 0.810~2.0J / cm 3 ;

[0069] The energy storage efficiency at 110° C. and 200 MV / m is greater than 91.0%, preferably 93.0 to 99.0%.

[0070] The third aspect of the present invention provides the use of the modified polypropylene dielectric energy storage material in the preparation of energy storage dielectrics; preferably, the use of the modified polypropylene dielectric energy storage material in the preparation of high-temperature energy storage dielectrics; the high-temperature energy storage dielectric is preferably an energy storage dielectric with a maximum operating temperature of ≥100°C;

[0071] The dielectric is preferably a single-layer or multi-layer film dielectric;

[0072] The membrane dielectric is preferably a capacitor film, an electrical film, a roughened film, a supercapacitor film, an electrostatic film or a battery separator, and is further preferably a capacitor film.

[0073] In the present invention, the thickness of the capacitor film is 0.5 to 15 microns, preferably 3 to 10 microns. The maximum operating temperature of the capacitor film is ≥ 100°C, preferably 105 to 145°C; - the breakdown field strength Eg of the capacitor film at 110°C is ≥ 580MV / m, preferably 600 to 800MV / m; the DC volume resistivity ρ of the capacitor film at 110°C and 200MV / m field strength is vg ≥1.1×10 14 Ω·m, preferably 2.1×10 14 Ω·m~1.0×10 20 Ω·m; the dielectric constant of the capacitor film at 110°C and 100 Hz is greater than 2.3, preferably 2.4 to 2.7; the dielectric loss of the capacitor film at 110°C and 100 Hz is less than 1.1×10 -3 , preferably 1.0×10 -6 ~9.5×10 -4 The energy storage density of the capacitor film at 110°C and 200MV / m is greater than 0.750J / cm 3 , preferably 0.810~2.0J / cm 3 The energy storage efficiency of the capacitor film at 110°C and 200 MV / m is greater than 91.0%, preferably 93.0-99.0%.

[0074] In the present invention, as a specific application example, for example, a polypropylene dielectric film is one layer or multiple layers, wherein at least a portion of at least one layer is a biaxially oriented polypropylene dielectric film (made by biaxially oriented the above-mentioned modified polypropylene dielectric energy storage material); or at least one layer is made of a raw material containing the above-mentioned modified polypropylene dielectric energy storage material, preferably made by biaxially oriented, and further preferably, at least one layer is made of the above-mentioned modified polypropylene dielectric energy storage material by biaxially oriented.

[0075] In the present invention, the method of preparing the polymer dielectric film from the modified polypropylene material pellets (the modified polypropylene dielectric energy storage material) can be carried out with reference to the prior art, for example, the pellets can be processed by hot pressing or extrusion casting, or by biaxial stretching to form a dielectric film. Preferably, the capacitor film is prepared by biaxial stretching.

[0076] As an example of a specific implementation method: the modified polypropylene material particles (the modified polypropylene dielectric energy storage material) prepared by the above method are added to the casting equipment for extrusion casting, and then the cast sheet is stretched in the film biaxial stretching equipment. In the process of extrusion casting, the casting die can be selected according to the structure of the film to be obtained. For example, when a film with a single-layer structure is required, a single-layer die can be used; when a film with a multi-layer structure (for example, a film with a three-layer structure of an upper surface layer, a core layer and a lower surface layer) is required, a multi-layer composite die can be used, and at least one layer (such as the core layer) of the multi-layer composite die is connected to the extruder hopper containing the modified polypropylene dielectric energy storage material, so that at least one layer (such as the core layer) of the obtained film is a modified polypropylene layer formed by the modified polypropylene dielectric energy storage material. In the extrusion process, the extrusion temperature can be 100-200°C, and the temperature of the casting chill roll can be 15-50°C.

[0077] In the present invention, the biaxial stretching includes synchronous stretching (i.e., stretching the film in the longitudinal direction (MD) and transverse direction (TD) at the same time) or stepwise stretching (i.e., first stretching the film in the longitudinal direction and then stretching the film in the transverse direction).

[0078] The synchronous stretching method includes: first preheating the modified polypropylene material casting sheet, the preheating temperature can be 120-170°C, and then simultaneously performing MD and TD stretching; the conditions of the synchronous stretching method include: the stretching temperature is 150-175°C, the MD stretching ratio is more than 3 times, the TD stretching ratio is more than 3 times, the MD stretching rate is 50-300% / s, and the TD stretching rate is 50-300% / s.

[0079] The step-by-step stretching method includes: preheating the modified polypropylene material casting sheet first, then performing MD stretching, and then preheating and then performing TD stretching; the conditions of the step-by-step stretching method include: MD stretching temperature is 150-170°C, TD stretching temperature is 155-175°C, MD stretching ratio is more than 3 times, TD stretching ratio is more than 5 times, MD stretching rate is 50-300% / s, and TD stretching rate is 50-300% / s.

[0080] According to the present invention, the method may or may not perform an annealing and shaping treatment on the stretched film. Preferably, the method of the present invention includes performing an annealing and shaping treatment on the stretched film, wherein, in the case of performing the shaping treatment, the temperature of the annealing and shaping treatment is preferably 160 to 180° C. The time of the annealing and shaping treatment is preferably 5 to 60 seconds. Performing the annealing and shaping treatment on the stretched film can improve the dimensional stability of the film.

[0081] According to the present invention, the method may further include subjecting the obtained polypropylene film to surface corona treatment, edge cutting and winding treatment. The surface corona treatment, edge cutting and winding treatment are conventional operations in the art and the present invention has no particular limitation on this.

[0082] The biaxially oriented polypropylene dielectric film and modified polypropylene dielectric energy storage material described in the present invention can be used as energy storage dielectrics. Since their operating temperature is very high, they are particularly suitable for use as high-temperature energy storage dielectrics. The dielectric is preferably a film dielectric, which can be a single layer or multiple layers, including but not limited to a capacitor film, an electrical film, a roughened film, a supercapacitor film, an electrostatic film or a battery separator. The polypropylene dielectric energy storage material of the present invention is particularly suitable for preparing a capacitor film. The capacitor film is a functional film material with polarization as the basic electrical characteristic, and is used as a dielectric material in a film capacitor due to its excellent insulation and dielectric properties. The electrical film is a film with a thickness of less than 350 microns and excellent electrical properties. It is usually made of high molecular polymers and may contain some auxiliary materials to meet the requirements of corrosion resistance and radiation resistance of electrical products. It is generally used in the insulation of electronic parts, automotive wiring, wire winding, insulation protection and other aspects.

[0083] The present invention is further described below by examples:

[0084] Test method:

[0085] 1. Determination of ash content of polypropylene / modified polypropylene materials:

[0086] The determination was carried out according to the method specified in GB / T 9345-2008.

[0087] 2. Determination of isotacticity of polypropylene:

[0088] The determination was carried out according to the method specified in GB / T 2412-2008.

[0089] 3. Determination of melt flow rate MFR:

[0090] According to the method specified in GB / T 3682-2018, the MFR of polypropylene / modified polypropylene materials was measured at 230°C and 2.16 kg load using a CEAST 7026 melt indexer.

[0091] 4. Determination of grafting amount:

[0092] The grafting amount refers to the content of the grafting unit of the polypropylene energy storage material in the present invention. 2-4g of the product is placed in a Soxhlet extractor and extracted with ethyl acetate for 24 hours to remove the unreacted monomer and its homopolymer, remove the unreacted monomer and its homopolymer, dry and weigh the sample, and calculate the parameter grafting amount. The formula is as follows:

[0093]

[0094] In the above formula, w 0 is the quality of PP raw materials; w 1 is the mass of the grafted product before extraction; w 2 It is the mass of the grafted product after extraction.

[0095] 5. Determination of DC volume resistivity:

[0096] The test was carried out according to the method specified in GB / T 13542.2-2009, the test method was the contact electrode method, the electrode material was conductive rubber, the test temperature was 110°C, and the test field strength was 200MV / m.

[0097] 6. Determination of breakdown field strength:

[0098] The test was carried out according to the method specified in GB / T 13542.2-2009, the test method was 50-point electrode method and the test temperature was 110°C.

[0099] 7. Determination of energy storage density and energy storage efficiency:

[0100] The measurement was performed according to the method specified in the following literature.

[0101] Yuan, C., Zhou, Y., Zhu, Y. et al. Polymer / molecular semiconductor all-organic composites for high-temperature dielectric energy storage. Nat. Commun. 11, 3919 (2020). The test temperature is 110°C and the test field strength is 200 MV / m.

[0102] 8. Determination of dielectric constant and dielectric loss factor:

[0103] The measurement was performed according to the method specified in the following literature.

[0104] Yuan, C., Zhou, Y., Zhu, Y. et al. Polymer / molecular semiconductor all-organic composites for high-temperature dielectric energy storage. Nat. Commun. 11, 3919 (2020). The test temperature is 110°C and the test frequency is 100 Hz.

[0105] Examples relate to raw materials

[0106] Polypropylene powder is shown in Table 1 (self-made according to the method of CN109694428A)

[0107] Table 1

[0108]

[0109]

[0110] Initiator

[0111] Benzoyl peroxide (BPO), Bailingwei Technology Co., Ltd.;

[0112] Tert-butyl peroxy-2-ethylhexanoate (TBPEH), Adamas Reagents Ltd.;

[0113] Dicumyl peroxide (DCP), Shanghai Aladdin Biochemical Technology Co., Ltd.;

[0114] 2,5-Dimethyl-2,5-bis(tert-butylperoxy)hexane (DHBP), J&K Technology Co., Ltd.;

[0115] Tert-butyl perbenzoate (TBPB), Bailingwei Technology Co., Ltd.;

[0116] Grafting monomer:

[0117] Styrene (St), Bailingwei Technology Co., Ltd.;

[0118] Methyl methacrylate (MMA), Bailingwei Technology Co., Ltd.;

[0119] Glycidyl methacrylate (GMA), Bailingwei Technology Co., Ltd.;

[0120] Methacrylic acid (MAA), Sinopharm Chemical Reagent Co., Ltd.;

[0121] Acrylic acid (MA), Sinopharm Chemical Reagent Co., Ltd.;

[0122] Maleic anhydride (MAH), Sinopharm Chemical Reagent Co., Ltd.;

[0123] Dispersant: xylene, Bailingwei Technology Co., Ltd.; acetone, ethanol, and n-heptane, all purchased from Sinopharm Chemical Reagent Co., Ltd.;

[0124] Antioxidants:

[0125] Antioxidant 1076, Antioxidant 1010, Antioxidant 168, Antioxidant 501, Shanghai Kaiyin Chemical; other additives

[0126] Lubricant: PP wax 2602 (Clariant), fluoropolymer (3M FX5920);

[0127] Experimental equipment

[0128] Twin screw extruder (HAAKE Rheomex PTW 16OS, L / D=40)

[0129] Example 1

[0130] 8.2g TBPEH, 37.3g TBPB and 360g methyl methacrylate were added to a conical flask and stirred magnetically in a water bath at 40°C for 15 minutes to prepare a uniform solution (mixed solution). 5.0kg PP1 powder (particle size of 0.5-2mm) screened out from the middle layer of a sieving machine equipped with 10-mesh and 35-mesh filters was added to a 50L jacketed steel kettle equipped with a spiral ribbon stirring paddle, and the reaction system was sealed and nitrogen was replaced for deoxygenation. The mixed solution was added to the steel kettle at a speed of 15.3ml / min, the temperature was 60°C, and the stirring rate was 80rpm. After the addition was completed, the raw materials continued to mix for 1.5 hours to obtain prefabricated PP powder (prefabricated polypropylene particles). 16.3g of antioxidant 1010, antioxidant 168 and antioxidant 501 (the mass ratio of antioxidant 1010, antioxidant 168 and antioxidant 501 is 1:1:0.04) are prepared into a uniform solution with 50ml of xylene, added to the above-mentioned steel kettle and stirred for 15 minutes to obtain a mixed raw material. The raw materials are added to a twin-screw extruder, and melt-mixed at a speed of 170°C, 180°C, 190°C, 200°C, 200°C, 200°C, 190°C, 185°C, and 180°C at each section of the extruder, extruded, cooled and pelletized to obtain 5.18kg of modified polypropylene dielectric energy storage material.

[0131] The pellets obtained above were placed in a hot air oven for drying, and the dried pellets were added into an extrusion casting machine model LCR400 purchased from Swedish Labtech for melt extrusion and casting. The temperature of the melt extruder was 220°C, the temperature of the screen changing zone was controlled at 220°C, the head temperature was controlled at 220°C, and the temperature of the casting roller was controlled at 25°C to produce a thick casting sheet of 220±15μm.

[0132] The above-mentioned polypropylene thick casting sheet was placed in the stretching fixture of the film biaxial stretching equipment and formed by a biaxial synchronous stretching process. The process conditions of each step included: preheating temperature of 165°C, stretching temperature of 165°C, stretching ratio of 5.5×5.5 times, film stretching rate of 150% / s; film setting temperature of 160°C. The electrical performance parameters of the obtained polypropylene film C1 were tested, and the results are shown in Table 1.

[0133] Example 2

[0134] 2.4g TBPEH, 54.8g DCP, 166g maleic anhydride, 100g styrene and 300ml acetone were added to a conical flask and stirred magnetically in a water bath at 40℃ for 20min to prepare a uniform solution (mixed solution). 5.0kg of PP2 powder with a particle size of 2.5 was screened out in the middle layer of a sieving machine equipped with 10 mesh and 35 mesh filters, and added to a 50L jacketed steel kettle equipped with a spiral ribbon stirring paddle, the reaction system was sealed, and nitrogen was replaced for deoxygenation. The mixed solution was added to the steel kettle at a speed of 13.6ml / min, the temperature was 40℃, and the stirring rate was 70rpm. After the addition was completed, the raw materials continued to mix for 1.5 hours to obtain prefabricated PP powder. 24.5g of antioxidant 1010, antioxidant 168 (the mass ratio of antioxidant 1010 to antioxidant 168 is 1:1) and 6g of PP wax were prepared into a uniform solution with 35ml of acetone, added to the above-mentioned steel kettle and stirred for 15min, and vacuumed for 30min to obtain a mixed raw material. The raw materials were added to a twin-screw extruder, and melt-mixed at the temperatures of each section of the extruder of 180℃, 190℃, 200℃, 210℃, 210℃, 210℃, 200℃, 190℃, and 185℃, and the speed was 165rpm, extruded, cooled and pelletized to obtain 5.17kg of modified polypropylene dielectric energy storage material.

[0135] The polypropylene film C2 was prepared in the same manner as in Example 1, and various electrical performance parameters were tested. The results are shown in Table 1.

[0136] Example 3

[0137] 1.1g TBPEH, 16.5g DCP, 263g methacrylic acid and 200ml ethanol were added to a conical flask and stirred magnetically in a water bath at 40℃ for 15min to prepare a uniform solution (mixed solution). 5.0kg of PP2 powder with a particle size of 2.5 was screened out in the middle layer of a sieving machine equipped with 10-mesh and 35-mesh filters and added to a 50L jacketed steel kettle equipped with a spiral ribbon stirring paddle. The reaction system was sealed and nitrogen was replaced for deoxygenation. The mixed solution was added to the steel kettle at a rate of 11.4ml / min, the temperature was 45℃, and the stirring rate was 60rpm. After the addition was completed, the raw materials continued to mix for 40 minutes to obtain prefabricated PP powder. 17.6g of antioxidant 1076, antioxidant 168, antioxidant 501 (the mass ratio of antioxidant 1076, antioxidant 168 and antioxidant 501 is 1:1:0.04) and 18g of fluorine-containing polymer are prepared into a uniform solution with 50ml of ethanol, added to the above-mentioned steel kettle and stirred for 25min, and vacuumed for 40min to obtain a mixed raw material. The raw materials are added to a twin-screw extruder, and melt-mixed at a speed of 180rpm at a temperature of 165℃, 175℃, 190℃, 200℃, 200℃, 200℃, 190℃, 180℃, and 175℃ in each section of the extruder, extruded, cooled and pelletized to obtain 5.11kg of modified polypropylene dielectric energy storage material.

[0138] The polypropylene film C3 was prepared in the same manner as in Example 1, and various electrical performance parameters were tested. The results are shown in Table 1.

[0139] Example 4

[0140] 1.3g TBPEH, 11.4g DCP, 210g styrene were added to a conical flask and stirred magnetically for 30min in a water bath at 40℃ to prepare a uniform solution (mixed solution). 5.0kg of PP3 powder with a particle size of 2.5 was screened out in the middle layer of a sieving machine equipped with 10-mesh and 35-mesh filters, and added to a 50L jacketed steel kettle equipped with a spiral ribbon stirring paddle, and the reaction system was sealed and nitrogen was replaced for deoxygenation. The mixed solution was added to the steel kettle at a speed of 6.7ml / min, the temperature was 50℃, and the stirring rate was 70rpm. After the addition was completed, the raw materials continued to mix for 1 hour to obtain prefabricated PP powder. 18.1g of antioxidant 1076, antioxidant 168 and antioxidant 501 (the mass ratio of antioxidant 1076, antioxidant 168 and antioxidant 501 is 1:1:0.04) are prepared into a uniform solution with 100ml of n-heptane, added to the above-mentioned steel kettle and stirred for 25min, and vacuumed for 20min to obtain a mixed raw material. The raw materials are added to a twin-screw extruder, and melt-mixed at a speed of 200rpm at a temperature of 180℃, 190℃, 200℃, 210℃, 210℃, 210℃, 200℃, 190℃, and 185℃ in each section of the extruder, extruded, cooled and pelletized to obtain 5.13kg of modified polypropylene dielectric energy storage material.

[0141] The polypropylene film C4 was prepared in the same manner as in Example 1, and various electrical performance parameters were tested. The results are shown in Table 1.

[0142] Example 5

[0143] 1.6g TBPEH, 4.0g DHBP, 174g glycidyl methacrylate and 200ml ethanol were added to a conical flask and stirred magnetically in a water bath at 40℃ for 15min to prepare a uniform solution (mixed solution). 5.0kg of PP2 powder with a particle size of 2.5 was screened out in the middle layer of a sieving machine equipped with 10-mesh and 35-mesh filters, and added to a 50L jacketed steel kettle equipped with a spiral ribbon stirring paddle, a closed reaction system, and nitrogen replacement for deoxygenation. The (mixed solution) was added to the steel kettle at a rate of 11.4ml / min, the temperature was 45℃, and the stirring rate was 60rpm. After the addition was completed, the raw materials continued to mix for 40 minutes to obtain prefabricated PP powder. 17.6g of antioxidant 1076, antioxidant 168, antioxidant 501 (the mass ratio of antioxidant 1076, antioxidant 168 and antioxidant 501 is 1:1:0.04) and 18g of fluorine-containing polymer are prepared into a uniform solution with 50ml of ethanol, added to the above-mentioned steel kettle and stirred for 25min, and vacuumed for 40min to obtain a mixed raw material. The raw materials are added to a twin-screw extruder, and melt-mixed at the temperatures of each section of the extruder of 165℃, 175℃, 190℃, 200℃, 200℃, 200℃, 190℃, 180℃, 175℃ and a speed of 170rpm, extruded, cooled and pelletized to obtain 5.09kg of modified polypropylene dielectric energy storage material.

[0144] The polypropylene film C5 was prepared in the same manner as in Example 1, and various electrical performance parameters were tested. The results are shown in Table 1.

[0145] Example 6

[0146] The "8.2 g TBPEH, 37.3 g TBPB" in Example 1 were replaced by "45.5 g TBPB", and the rest were the same as Example 1, to obtain 5.15 kg of modified polypropylene dielectric energy storage material, to prepare polypropylene film C6, and to test the obtained electrical performance parameters. The results are shown in Table 1.

[0147] Example 7

[0148] 5.0 kg of unscreened PP1 powder was mixed evenly with 8.2 g of TBPEH, 37.3 g of TBPB, 360 g of methyl methacrylate, 16.3 g of antioxidant 1010, antioxidant 168, antioxidant 501 (the mass ratio of antioxidant 1010, antioxidant 168 and antioxidant 501 is 1:1:0.04) and 50 ml of xylene in a solid-liquid mixer, and then added into a twin-screw extruder. The mixture was melt-kneaded at a speed of 170 rpm and each section of the extruder was at temperatures of 170°C, 180°C, 190°C, 200°C, 200°C, 200°C, 190°C, 185°C and 180°C, respectively. The mixture was extruded, cooled and pelletized to obtain 5.12 kg of modified polypropylene particles.

[0149] The polypropylene film C7 was prepared in the same manner as in Example 1, and various electrical performance parameters were tested. The results are shown in Table 2.

[0150] Table 2

[0151]

[0152] It can be seen from the examples that the preparation method of the present invention is applicable to a wide range of raw materials, and the biaxially stretched film prepared from the obtained material has the above-mentioned excellent dielectric properties measured at 110°C. For example, the energy storage efficiency of the measured film at 110°C and 200MV / m is greater than 91%, which can be used as an indication of the maximum working temperature. It can be confirmed that the capacitor film of the present invention has a maximum working temperature of at least 110°C. Good dielectric and energy storage performance, suitable for use as energy storage materials, especially for the use of capacitor films and electrical films. By comparing Example 1 and Example 6, it can be seen that the compound use of initiators with different decomposition temperatures can effectively inhibit the side reactions in melt grafting, so that the material can obtain more excellent performance. By comparing Example 1 and Example 7, it can be seen that the use of raw material processing methods such as particle size screening and premixing during feeding can effectively improve the diffusion and dispersion uniformity of the initiator and grafted monomer in the resin, so that the material can obtain more excellent dielectric energy storage performance. It can be seen from Examples 4 and 5 that the material performance obtained by using polypropylene with high ash content or using non-preferred initiator formula is slightly lower.

[0153] The embodiments of the present invention have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and changes will be apparent to those skilled in the art without departing from the scope and spirit of the described embodiments.

Claims

1. A method for preparing a modified polypropylene dielectric energy storage material, characterized in that: The preparation method comprises: mixing and melt-kneading polypropylene, a grafting monomer, an initiator, an antioxidant, a dispersant and other optional additives to obtain the modified polypropylene dielectric energy storage material; Wherein, the ash content of the polypropylene is less than 55 ppm, preferably less than 40 ppm, and more preferably less than 36 ppm.

2. The preparation method according to claim 1, wherein The preparation method comprises: (1) stirring the grafting monomer, the initiator and optionally a portion of the dispersant to obtain a mixed solution; (2) mixing the polypropylene and the mixed solution to obtain prefabricated polypropylene particles; (3) The antioxidant, the remaining dispersant and the other additives are mixed; then mixed with the prefabricated polypropylene particles, melt-kneaded, and the modified polypropylene dielectric energy storage material is obtained.

3. The preparation method according to claim 1 or 2, wherein The melt flow rate of the polypropylene at 230° C. and a load of 2.16 kg is 0.01 to 10 g / 10 min, preferably 0.5 to 10 g / 10 min, and more preferably 2 to 5 g / 10 min.

4. The preparation method according to claim 1 or 2, wherein: The grafting monomer is at least one of aromatic olefins, acid anhydrides, acrylic acid and acrylic esters; preferably at least one of styrene, maleic anhydride, glycidyl methacrylate, methyl methacrylate and acrylic acid.

5. The preparation method according to claim 1 or 2, wherein: The initiator is a peroxide and / or an azo type; Preferably, the peroxidation initiator comprises at least one of benzoyl peroxide, dichlorobenzoyl peroxide, dialkyl peroxide, aralkyl peroxide, peroxyester and peroxycarbon ester; preferably, it is a combination of one or more of diisopropylbenzene peroxide, tert-butyl peroxy-2-ethylhexanoate, di-tert-butyl peroxide and tert-butyl peroxybenzoate; more preferably, it is a combination of tert-butyl peroxy-2-ethylhexanoate and tert-butyl peroxybenzoate or a combination of tert-butyl peroxy-2-ethylhexanoate and diisopropylbenzene peroxide.

6. The preparation method according to claim 1 or 2, wherein: The antioxidant is selected from at least one of hindered phenols, hindered amines, phosphites, thiols and benzofuranones; Preferably, the antioxidant is compounded from an antioxidant component A and an antioxidant component B, wherein the antioxidant component A is selected from at least one of hindered phenols, hindered amines, phosphites and thiols, and the antioxidant component B is at least one benzofuranone; More preferably, it is at least one of the antioxidant 1010 , the antioxidant 168 , and the antioxidant 501 .

7. The preparation method according to claim 1 or 2, wherein: The melt kneading temperature is 120 to 250° C., preferably 130 to 220° C., and more preferably 160 to 220° C.; The polypropylene is preferably a polypropylene powder with a particle size of 0.5 to 2 mm; In parts by mass, relative to 100 parts of the polypropylene, the amount of the grafting monomer is 0.1 to 30 parts, preferably 2 to 15 parts, the amount of the initiator is 0.001 to 10 parts, preferably 0.1 to 2 parts, the amount of the antioxidant is 0.1 to 0.8 parts, preferably 0.1 to 0.6 parts, the amount of the dispersant is 0.01-10 parts and the amount of the optional other auxiliary agents is 0 to 1 part, preferably 0 to 0.

6.

8. A modified polypropylene dielectric energy storage material prepared according to the preparation method according to any one of claims 1 to 7.

9. The modified polypropylene dielectric energy storage material according to claim 8, wherein: The modified polypropylene dielectric energy storage material has at least one of the following physical properties: a melt flow rate of 1 to 10 g / 10 min, preferably 1.5 to 8 g / 10 min, and more preferably 2 to 5 g / 10 min at 230° C. and a load of 2.16 kg; Ash content less than 50 ppm, preferably less than 36 ppm; The grafting amount is 0.01 to 10 wt%, preferably 0.1 to 8 wt%; The maximum operating temperature of the modified polypropylene dielectric energy storage material is ≥100°C, preferably 105-145°C; The breakdown field strength at 110°C is Eg ≥ 580 MV / m, preferably 600-800 MV / m; DC volume resistivity ρ at 110℃ and 200MV / m field strength vg ≥1.1×10 14 Ω·m, preferably 2.1×10 14 Ω·m~1.0×10 20 Ω·m; The dielectric constant at 110°C and 100 Hz is greater than 2.3, preferably 2.4 to 2.7; The dielectric loss at 110℃ and 100Hz is less than 1.1×10 -3 , preferably 1.0×10 -6 ~9.5×10 -4 ; The energy storage density at 110°C and 200MV / m is greater than 0.750J / cm 3 , preferably 0.810~2.0J / cm 3 ; The energy storage efficiency at 110° C. and 200 MV / m is greater than 91.0%, preferably 93.0 to 99.0%.

10. Use of the modified polypropylene dielectric energy storage material according to claim 8 or 9 in the preparation of energy storage dielectrics; preferably in the preparation of high-temperature energy storage dielectrics; The dielectric is preferably a single-layer or multi-layer film dielectric; The membrane dielectric is preferably a capacitor film, an electrical film, a roughened film, a supercapacitor film, an electrostatic film or a battery separator, and is further preferably a capacitor film.